DISEÑO TECNOLÓGICO PRELIMINAR DE UNA PLANTA DE PEAD A TRAVÉS DE LA RUTA ALCOQUÍMICA, EN CONDICIONES DE INCERTIDUMBRE - Morales Hernández, Yanilka; Matos Mosqueda, Luisa; Crespo Zafra, Lourdes (Centro Azúcar Journal, 2007)
The following work was carry out for designing a technological preliminary plant of high-density Polyethylene (PEAD) starting from ethylene obtained by alkochemical way. Keeping in mind a demand study in the cities of Ciego de Avila, Camagüey and to national scale. The design of the main equipment of the plant, was carried out by means of the Method of Classic Design to diminish the uncertainly in the process, was used a factor of sobrediseño of 20%, value which is recommended by Rudd and Watson for this method, and the determination of the capacity was done by means of the Method of the Initial Null Demand. Finally a technical- economic analysis was developed to determine if it is feasible the construction of the plant. The main results of this analysis demonstrate that it is economically feasible.